Volume and taper equations for Sitka spruce (Picea sitchensis (Bong.) Carr.), Norway spruce (Picea abies (L.) Karst.) and White spruce (Picea glauca (Moench) Voss) in Iceland - Heidarsson, Larus (SLU/Dept. of Forest Resource Management, 2014)
The aim of this study was to evaluate different types of volume and taper equations that can be used to predict single-tree stem volume and stem diameter at any given height along the tree stem for plantation grown Sitka spruce (Picea sitchensis (Bong.) Carr.), Norway spruce (Picea abies (L.) Karst) and White spruce (Picea glauca (Mounch) Voss) in Iceland. A number of published tree volume equations were tested and modified to predict the total stem volumes over bark but three logarithmic equations were taken for more in-depth analysis. Three taper equations were tested. Two variable-exponent equations (Kozak 1997, Kozak 2004) and one exponential equation described by Biging (1984). Data from a total of 617 sample trees were used in this study, collected from stands in various parts of the country and present different types of stands growing in different soil types and cover most of the site conditions suitable for forestry in Iceland. To fit the regression model for the volume equations an ordinary least-squares (OLS) method was used. Because the construction of taper equations requires longitudinal data or multiple measurements on individual trees, and violates the assumption of independence between observations, a mixed effects approach was used to model the within tree autocorrelation. Volume equation [5] which has breast height diameter (D), tree height (H) and (H-1.3) as independent variables gave the best results based on fit and validation statistics and are most suitable for all three species. In diameter prediction a modified version of the Biging (1984) equation gave the best results based on fit and validation statistics and is most suitable for all three species. In volume prediction the Biging (1984) equation showed some bias in predicting volume of small trees and the same was noticed for the equation developed by Kozak (1997). The equation developed by Kozak (2004) seems to be more flexible in predicting the volume of small trees as well as bigger trees and should give the best results in volume ...